Determinants of medication non-adherence among patients with chronic diseases at community pharmacy settings in South Gondar Zone, Northwest Ethiopia: a multicenter cross-sectional study - Moges, Tilaye Arega; Dagnew, Samuel Berihun; Wondm, Samuel Agegnew; Ferede, Yared Andargie; Yiblet, Tesfagegn Gobezie; Almaw, Andargachew; Shumet Yimer, Yohannes; Tesfaw Addis, Getu; Zewdu, Woretaw Sisay; Dagnew, Fisseha Nigussie (Frontiers in Public Health, 2024)
Background: Medication non-adherence is a significant public health concern in managing patients with chronic diseases, and community pharmacists are on the frontline in the management of chron ic diseases. Chronic diseases require lifelong pharmacotherapy; understanding the determinants of medication adherence is of paramount importance to develop strategies that improve medication ad herence and treatment outcomes. Thus, this study aimed to assess the magnitude of medication nonadherence and its contributing factors among patients with chronic diseases attending community pharmacies in South Gondar Zone, Northwest Ethiopia.Gondar Zone from September 01 to October 30, 2023. Medication adherence was assessed using a structured questionnaire using the Adherence in Chronic Diseases Scale (ACDS). Statistical Package for Social Sciences (SPSS) version 25 was used for analysis. Association between the outcome variable and independent variables was performed using binary logistic regression and a p-value of <0.05 was considered statistically significant.Results: From 386 study participants recruited in this study, more than half of them 222 (57.51%) at 95%CI (52.4% -62.5%) were low-adherent to their medications. Concerning determinants of medication non-adherence, the presence of side effects (AOR =2.1, 95% CI=1.33-3.29), unable to get ever counseling from community pharmacists (AOR=2.3, 95%CI= 1.46-3.58), and poor about their medications (AOR=3.1, 95% CI= 1.96-4.82) were significantly associated with patients' nonadherence to medications.Our study of medication adherence among chronic disease patients attending commu nity pharmacies found that adherence rates were suboptimal. The presence of side effects, unable to get ever counseling, and poor knowledge about their medications were statistically significant fact ors of poorer medication adherence. Hence, healthcare professionals, especially community pharm acists, have a crucial role in designing the schedule for health education concerning the needs of these patients in community pharmacy settings.